2015
DOI: 10.1590/1516-3180.20151333t2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced dietary salt for the prevention of cardiovascular disease

Abstract: BACKGROUND: This is an update of a Cochrane review that was first published in 2011 of the effects of reducing dietary salt intake, through advice to reduce salt intake or low-sodium salt substitution, on mortality and cardiovascular events. OBJECTIVES: 1. To assess the long-term effects of advice and salt substitution, aimed at reducing dietary salt, on mortality and cardiovascular morbidity. 2. To investigate whether a reduction in blood pressure is an explanatory factor in the effect of such dietary interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…This topic has been controversial for a long time (Volatier & Lafay, ). In particular, there are major differences in the responses of blood pressure to salt intake between normotensive and hypertensive subjects (Adler et al., ; Mente et al., ; Volatier & Lafay, ). The debate remains ongoing because HBP is linked to many other dietary factors (Institute of Medicine (USA) Panel on Dietary Reference Intakes, ).…”
Section: Effects Of Salt On Human Heathmentioning
confidence: 99%
“…This topic has been controversial for a long time (Volatier & Lafay, ). In particular, there are major differences in the responses of blood pressure to salt intake between normotensive and hypertensive subjects (Adler et al., ; Mente et al., ; Volatier & Lafay, ). The debate remains ongoing because HBP is linked to many other dietary factors (Institute of Medicine (USA) Panel on Dietary Reference Intakes, ).…”
Section: Effects Of Salt On Human Heathmentioning
confidence: 99%
“…In a review of studies examining the interaction between salt reduction and blood pressure, a significant reduction in both systolic (−7.11 mmHg, 95 % CI −8.81, −5.41, p < 0.0001) and diastolic blood pressure (−3.41, 95%CI −4.29, −2.53, p<0.0001) was seen in both hypertensive and normotensive women with a reduction of salt intake below 5-6 g/day [43]. Although higher salt intake is associated with worse cardiovascular outcomes [44], measures such as advice to reduce salt intake or salt substitutes are only weakly associated with an improvement in cardiovascular mortality and cardiovascular events [45].…”
Section: Diet Changesmentioning
confidence: 95%
“…Further analysis of the same dataset revealed a linear 17 % increase in risk of cardiovascular events for every 1 g/ day increase in sodium excretion, albeit of borderline statistical significance (p = 0.054) [74]. These findings have been challenged by a subsequent Cochrane review, including two additional randomized trials [75], which concluded that current data are insufficient to determine if dietary sodium restriction affects cardiovascular morbidity or mortality.…”
Section: Sodium Intake and Hf Risk In Cohort Studiesmentioning
confidence: 99%